1996
DOI: 10.2307/4002676
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes of Herbage Biomass on the Fescue Prairie

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 10 publications
(10 reference statements)
2
17
0
Order By: Relevance
“…The grasses tested in this study could not account for the biomass losses of 53% or more observed on the fescue grassland community (Willms et al 1996). This indicates that other plants, probably represented mostly by forbs, are more degradable and may disappear almost completely.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The grasses tested in this study could not account for the biomass losses of 53% or more observed on the fescue grassland community (Willms et al 1996). This indicates that other plants, probably represented mostly by forbs, are more degradable and may disappear almost completely.…”
Section: Discussionmentioning
confidence: 60%
“…Smooth aster, as a model of a forb, seemed to degrade more rapidly than grasses in the litter mass (Table 5) and is more susceptible to physical erosion when suspended on a stem. Loss of forb biomass was almost 60% compared with 27% for grasses (Willms et al 1996).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Areas with a history of grazing are generally characterized by reduced litter (Willms et al 1986), decreased annual production, increased losses of herbage over winter, and delayed spring growth (Willms et al 1996). The maximum seasonal phytomass of each herbage component documented in summer coincided with wet soil conditions.…”
Section: Discussionmentioning
confidence: 99%
“…High herbage yield in summer was dependent on precipitation during the growing season. Shallow-rooted, rhizomatous species (like those dominant in this community) are most productive with frequent showers since moisture conservation tends to be inefficient with reduced litter (Willms et al 1996). Clipping or grazing can also change the distribution of roots in the soil by reducing the rooting depth and packing more roots in the soil surface (Willms 1991;Smoliak et al 1972).…”
Section: Discussionmentioning
confidence: 99%